Antibacterial Activity of Aquatic Zea Mays L. Hairs Extract against Different Bacteria in Babylon Province: An In-Vitro Study - Rasha Hadi Saleh (Journal of Global Pharma Technology, 2017)
Background Zea Mays L. has been frequently used as a therapeutic agent used for treatment of various diseases .Objective A evaluation the antibacterial, anti-biofilm, adherence and swarming in hibitory activities of Zea Nujm mays L. hair extract against different bacteria. Methods: Well diffusion method, bio film inhibition test using a tissue culture plate, adherence and swarming inhibition assays were done for estimation and evaluation the anti-bacteriala activity of Zea mays L against a number of bacteria. Results: The result showed that Zea Mays L hair extracts the vying potent antibacterial activity. It’s also inhibiting adherence to epithelial cells and biofilm formations of the bacteria. The result shows that the extract has high anti-swarming activity .Conclusions: The extract has marked antibacterial activity. It can inhibit biofilm formation, swarming to ility, and bacterial cell adherence to oral epithelial cells. Keywords: Biofilm, Bacterial adherence, Swarming.